2021
DOI: 10.7717/peerj.11553
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the stoichiometry of Castanopsis fargesii along an elevation gradient in a Chinese subtropical forest

Abstract: Elevation is important for determining the nutrient biogeochemical cycle in forest ecosystems. Changes in the ecological stoichiometry of nutrients along an elevation gradient can be used to predict how an element cycle responds in the midst of global climate change. We investigated changes in concentrations of and relationships between nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), and magnesium (Mg) in the leaves and roots of the dominant tree species, Castanopsis fargesii, along an elevation gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
1
1
Order By: Relevance
“…These changes can subsequently influence leaf shape and physiological traits, including leaf thickness, which can have an impact on the concentration of leaf elements (Li et al, 2021; Zhou et al, 2013). Liu, Zheng, et al (2021) found that K and Ca in Castanopsis fargesii leaves were significantly correlated with ALT, while Mg had no significant relationship with ALT, which is different from the results of this study. The inconsistency in results could potentially be attributed to temperature variations.…”
Section: Discussioncontrasting
confidence: 99%
“…These changes can subsequently influence leaf shape and physiological traits, including leaf thickness, which can have an impact on the concentration of leaf elements (Li et al, 2021; Zhou et al, 2013). Liu, Zheng, et al (2021) found that K and Ca in Castanopsis fargesii leaves were significantly correlated with ALT, while Mg had no significant relationship with ALT, which is different from the results of this study. The inconsistency in results could potentially be attributed to temperature variations.…”
Section: Discussioncontrasting
confidence: 99%
“…Relationships between leaf stoichiometry and environmental factors, including soil nutrients and geographical and climatic factors, were widely explored at various scales including regional and global scales (e.g., McGroddy et al, 2004 ; Reich and Oleksyn, 2004 ; Sardans et al, 2011 ; Du et al, 2017 ; Tian et al, 2018 ; Qin et al, 2021 ). Elevation is a crucial factor and can affect plant leaf stoichiometry by altering the combination of heat and water, soil properties, and vegetation community composition (Bo et al, 2020 ; Liu et al, 2021 ). However, there is little consensus on leaf stoichiometric characteristics as they change along an elevation gradient.…”
Section: Introductionmentioning
confidence: 99%